Supply Bottlenecks : Where, Why, How Much, and What Next? - Celasun, Oya (IMF Working Papers; Working Paper ;, 2022)
Supply constraints hurt the economic recovery and boosted inflation in 2021. We find that in the euro area, manufacturing output and GDP would have been about 6 and 2 percent higher, respectively, and half of the rise in manufacturing producer price inflation would not have occurred in the absence of supply bottlenecks. Globally, shutdowns can explain up to 40 percent of the supply shocks. Sectors that are more reliant on differentiated inputs-such as autos-are harder hit. Late last year industry experts expected supply shortages for autos to largely dissipate by mid-2022 and broader bottlenecks by end-2022, but given the Omicron wave, disruptions will last for longer, possibly into 2023. With supply constraints adding to price pressures, the challenge for policymakers is to support recovery without allowing high inflation to become entrenched.